Reversible CO2 activation by an N-phosphinoamidinato digermyne - Quek, Shina (Nanyang Technological University, 2022)
This thesis describes the synthesis of the N-phosphinoamidinato digermynes [LG̈e–G̈eL] (E = Ge, L = tBu2PNC(Ph)NAr, 5: Ar = 2,6-iPr2C6H3, 6: Ar = Ph) by the reduction of the corresponding chlorogermylenes with KC8. Compounds 5 and 6 underwent reversible oxidative addition with CO2 in toluene at room temperature to form [LG̈eOC(O)G̈eL] (9: Ar = 2,6-iPr2C6H3, 10: Ar = Ph). The reversibility was rationalized by NMR spectroscopy and DFT calculations. Compound 10 demonstrated the capability of executing sequential elementary organometallic processes with multiple substrates in its reaction with CO2 and phenylacetylene, as well as CO2 and hexafluorobenzene to form [LG̈eC(Ph)=C(Ph)G̈eL] (11), [LG̈eF] (12) and [LG̈eC6F5] (13), respectively.